The Development of E-Learning Chemistry Learning for SMA / MA based on Project Based Learning on Quantum Number Material with the Flipped Classroom Approach in Class X Senior High School - Alaa Ameen Muhammad Saeed Aledressi; Marla Ma'firah; Yosi Juwita Erman; Ifan Rivaldo; Nurhawilis Nurhawilis (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2021)
Educational Chemistry is a material which in its study requires 3 levels of representation known as the triangle, namely macroscopic, submicroscopic and symbolic. At the microscopic level, chemical materials study abstract things such as atoms, molecules, compounds so that they must be a concrete picture to study them. At the symbolic level contains formulas, structures, and reaction equations. Meanwhile, at the macroscopic level it was carried out by means of experiments. However, in its implementation, the experiment requires a long time and complete facilities and infrastructure. So that what happens in the field students only remember and memorize, do not understand and have the ability to think at a high level in accordance with the demands of the 2013 curriculum. There have been many studies that have shown that these learning models are able to improve students' higher order thinking skills (HOTS) and creative thinking. So that the authors make this research into the Development of a Content Learning System (CLS) Flipped Classroom Model Based on Project Base Learning on Quantum Number in 1st Class (X) term to Improve Higher-Level Thinking Ability. This research is a research development (R&D) using the Borg and Gall model.